Interleukin-17-Producing CD4+ T Cells Promote Inflammatory Response and Foster Disease Progression in Hyperlipidemic Patients and Atherosclerotic Mice - Wang, Yin; Li, Wenming; Zhao, Tingrui; Zou, Yao; Deng, Tao; Yang, Zhangyou; Yuan, Zhiyi; Ma, Limei; Yu, Ruihong; Wang, Tingting; Yu, Chao (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a chronic inflammatory disease. Interleukin-17-producing CD4+ T cells (Th17 cells) play important roles in the progression of atherosclerosis. However, most of the studies were focused on the advanced stages of atherosclerosis. In the current study, we investigated the roles of Th17 cells and relevant mechanisms in hyperlipidemic patients and different stages of atherosclerotic mice. Human blood samples were collected and percentages of Th17 cells, macrophages and neutrophils were analyzed by flow cytometry. ApoE-/- mice were fed with high fat diet and sacrificed at different time points to evaluate the infiltration of inflammatory cells at different stages of atherosclerosis. Furthermore, essential mechanisms of IL-17A in atherosclerotic inflammatory milieu formation were studied in vivo by intraperitoneal injection with monoclonal anti-murine IL-17 antibody. Our study reveals the higher percentages of Th17 cells, monocytes and neutrophils in hyperlipidemic patients compared to healthy donors. Meanwhile, we also identify an infiltration of Th17 cells in early stage of atherosclerosis (4 weeks after high-fat diet (HFD)), which maintains at high level until late stage of atherosclerosis (20 weeks after HFD). What’s more, inflammatory cells including macrophages and neutrophils were also accumulated in atherosclerotic lesions. Neutralization of IL-17 in ApoE-/- mice resulted in less infiltration of macrophages and neutrophils and smaller atherosclerotic lesions. Importantly, in accordance with what found in mouse model, positive correlations between Th17 cells and macrophages or neutrophils were observed in hyperlipidemic patients. In conclusion, our clinical and mouse model data together reveal a pro-atherogenic role of Th17 cells through promotion of inflammation in hyperlipidemic conditions and different stages of atherosclerosis, which further supports the notion that IL-17 may by a therapy target for the treatment of atherosclerosis.